Factors affecting non‐operative management of uncomplicated appendicitis in children: Should laparoscopic appendectomy be immediate, interval, or emergency?. Issue 4 (11th December 2018) - Miyano, Go; Ochi, Takanori; Seo, Shogo; Nakamura, Hiroki; Okawada, Manabu; Doi, Takashi; Koga, Hiroyuki; Lane, Geoffrey J.; Yamataka, Atsuyuki
Abstract: Introduction: We conducted a prospective non‐randomized comparison of children with uncomplicated appendicitis treated either by primary laparoscopic appendectomy (PLA) or by non‐operative management (NOM) followed by interval laparoscopic appendectomy (ILA) if NOM was successful or emergency laparoscopic appendectomy (ELA) if NOM was unsuccessful. Methods: Before 2015, all patients with uncomplicated appendicitis underwent PLA using a standard three‐port technique. Postoperatively, piperacillin/tazobactam was administered until the white blood cell count was less than 10 000/μL and patients were afebrile. Since 2015, in cases of uncomplicated appendicitis, intravenous analgesia has been administered once after assessment, and then NOM has been immediately employed, with repeat doses of piperacillin/tazobactam administered every 8 h after admission. We have also used standard management cut‐off criteria to determine when to perform laparoscopic appendectomy after NOM: if NOM fails, ELA is performed within 6 h, and if NOM is successful, ILA is planned. Results: There were 103 eligible subjects for this study. Eleven cases of suspected complicated appendicitis were excluded, leaving 34 PLA cases and 58 NOM cases. After NOM, 27 patients were treated with ILA and 31 with ELA. There was one recurrence after successful NOM, and in two cases, patients' parents refused to consent to ILA after successful NOM. There were more perforations and significantly more residual abscesses in ELA than in PLA. Operative time and postoperative hospitalization were significantly longer among ELA patients than among PLA patients, and operative time was significantly shorter during ILA than in PLA. Conclusion: Further evaluation is required to confirm which patients will benefit most from NOM and what role PLA has in treating uncomplicated appendicitis.